Modelling of the Noise Processes - Rastislav Lukac; Viktor Fischer; Pavol Galajda (Communications, 2002)
In this paper, the modelling of noise processes and their application to image processing are described. Thus, the noise effect on useful image information is presented and analysed according to mathematical formulas, the reason of its origin, introduced visual changes and the possibility of their reduction. In order to provide an unbiased view on the noise effect, noise models are supported by a number of object-lesson figures.